2011
DOI: 10.1002/eji.201141899
|View full text |Cite
|
Sign up to set email alerts
|

CD22 serves as a receptor for soluble IgM

Abstract: CD22 (Siglec-2) is a B-cell membrane-bound lectin that recognizes glycan ligands containing a2,6-linked sialic acid (a2,6Sia) and negatively regulates signaling through the B-cell Ag receptor (BCR). Although CD22 has been investigated extensively, its precise function remains unclear due to acting multiple phases. Here, we demonstrate that CD22 is efficiently activated in trans by complexes of Ag and soluble IgM (sIgM) due to the presence of glycan ligands on sIgM. This result strongly suggests sIgM as a natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
(47 reference statements)
1
27
0
1
Order By: Relevance
“…have suppressive feedback effects, as was previously suggested for IgM Abs in a different context (1,41,(49)(50)(51)(52)(53). In the present study, a desialylated monoclonal anti-TNP IgM Ab enhanced TNP-Ficollinduced B cell activation in vivo.…”
Section: Figuresupporting
confidence: 85%
“…have suppressive feedback effects, as was previously suggested for IgM Abs in a different context (1,41,(49)(50)(51)(52)(53). In the present study, a desialylated monoclonal anti-TNP IgM Ab enhanced TNP-Ficollinduced B cell activation in vivo.…”
Section: Figuresupporting
confidence: 85%
“…Furthermore, they showed the absence of FcmR in human monocytes and that it is not induced by M-CSF. Moreover, by showing that passively adsorbed IgM or their pentavalent Fc portion did not modulate TNF-a secretion induced by suboptimal amounts of HAGG, we definitively excluded that IgM could influence the IgG-mediated cytokine-inducing signaling events after binding to very recently proposed (51,52) or as yet undescribed receptors. Using the HUL IgM RF, we previously reported that the IC formed during the successive (instead of simultaneous) incubation of C-FBG with first the ACPA + IgG then the IgM RF did not result in increased TNF-a secretion (33).…”
Section: Discussionmentioning
confidence: 78%
“…CD22 is a 140-kDa glycoprotein on the B cell surface and can be activated in trans on adjacent cells or cis on the same cell surface by different ligands including soluble IgM, CD45 and CD22 itself 46,47 . Clearly, WT CD11b can directly interact with CD22.…”
Section: Discussionmentioning
confidence: 99%